Edukasi Sumber Alami Antioksidan dan Manfaatnya bagi Kesehatan di Desa Sungai Lantuang - Verawati, Verawati; Fitrianda, Eka; Wahyuni, Rina (Universitas Pahlawan Tuanku Tambusai, 2025)
Antioxidants are natural or man-made substances that can prevent or delay some types of cell damage due to oxidation processes by free radicals in the body. Antioxidants are found in many foods, including fruits and vegetables. This community service aims to provide knowledge about natural sources of antioxidants and their benefits for health. This service activity was carried out for people who live in Sungai Latuang Village, Jambak Village, Batipuah Panjang Village, Padang City. The method used in this activity was counseling using the help of laptop and infocus devices. In addition to counseling, brochures and discussion sessions were also distributed as feedback to examine the participants' understanding of the material presented. Through this community service activity, there has been an increase in public understanding of the concept of antioxidants, natural sources of plants that are rich in antioxidant compounds, and their benefits for body health. This activity was attended by ± 30 people. Knowledge about natural antioxidants can add to people's insight into the importance of antioxidants in maintaining body health.